Long-Term Consequences of High Titer Neutralizing Antibodies to Interferon-β in Multiple Sclerosis - Dunn, Nicky; Fogdell-Hahn, Anna; Hillert, Jan; Spelman, Tim (Frontiers in Immunology, 2020)
Background Neutralizing anti-drug antibodies (NAbs) to interferon beta (IFNβ) develop in up to 47% of multiple sclerosis (MS) treated patients inhibiting treatment effect of IFNβ. However, the long-term effect of NAbs remain unknown. Objective To investigate the long-term consequences of high titer NAbs to IFNβ on disease activity and progression in MS patients. Methods An observational study including data from all IFNβ treated relapsing remitting MS patients with sufficient NAb test results from the Swedish MS registry. Patients were classified into either confirmed ‘high titer’ or ‘persistent negative’ groups and analyzed for differences in disease activity and progression over time. Results A total of 197 high-titer and 2907 persistent negative patients with 19969.6 follow up years of data were included. High titer NAbs were associated with a higher degree of disease activity at baseline. However, even when accounting for this, the presence of high titer NAbs were also associated with higher disease activity during IFNβ treatment. This persisted even after the next DMT start, suggesting that earlier high titers may partially reduce the effect of later treatments. No difference was found in confirmed disability progression. Conclusion High titer NAbs to IFNβ are associated with higher disease activity, persisting even after IFNβ discontinuation or switch. These results support use of highly efficient treatment earlier in patients with active disease, to avoid these complications.